Conducting a Successful Livestock Show for Youth - Chad Carr; Justin Crosswhite; Jennifer Shike; Heather Shultz (EDIS, 2011)
Want to plan a livestock show for youth that will serve as the educational summit of the livestock project experience? Make sure the entire event is as stress-free as possible for the livestock, youth exhibitors, their families, and show management, and as educational as possible for youth exhibitors, their families, and all public spectators. Consider the recommendations in this 4-page fact sheet written by Chad Carr, Justin Crosswhite, Jennifer Shike, and Heather Shultz, and published by the UF Department of Animal Science, December 2011.